Damage assessment for structure subjected to earthquake using wavelet packet decomposition and time-varying frequency. (December 2021) - He, Haoxiang; Chen, Yifei; Lan, Bingji
Abstract: The seismic damage assessment method based on frequency change rate is applied with the advantages such as clear mechanism and high precision, but the time resolution and the frequency resolution cannot be accurately meet at the same time when the traditional methods for signal analysis are used. Thus, the time-varying frequencies cannot be obtained directly from the response signals and the application of this damage assessment method is insufficient. The corresponding accuracy evaluation criterion for different signal analysis methods is presented based on the marginal condition in time-frequency domain, and wavelet packet decomposition method with special wavelet basis functions is verified as an efficient tool in establishing time-varying power spectrum on the basis of theoretical and computational analysis. The time-varying frequency extraction method based on wavelet packet ridge is proposed, and the time-varying seismic damage index can be calculated according to frequency changes, furthermore, the multi-dimensional seismic damage assessment can be realized. The numerical examples and experimental results show that the damage assessment method based on wavelet packet transform and time-varying frequency can accurately reveal the integral damage evolution process and the damage states. This method only requires structural response histories, and has superior adaptability on structural dynamic analysis, seismic design verification and seismic damage assessment for actual structures.